Infective Spondylitis with Epidural Abscess Formation Caused by Roseomonas mucosa: A Case Report and Literature Review - Zong-Han Lin; Yu-Chang Lu; Kuan-Sheng Wu (Case Reports in Infectious Diseases, 2023)
Roseomonas mucosa (R. mucosa) is a pink-pigmented, aerobic, nonfermentative, slow-growing Gram-negative coccus typically isolated from the natural environment, human skin, and hospital environment. This pathogen, in most circumstances, leads to infections in immunocompromised hosts, but it may sometimes invade immunocompetent individuals. Bacteraemia is the most common form of infection caused by R. mucosa. In contrast, only two case reports have described R. mucosa-related epidural abscess formation and infective spondylitis. In this case report, we shared the history and treatment experience of a 76-year-old female who was diagnosed with infective spondylitis and epidural abscess caused by R. mucosa. She received a local transdermal injection into the lower back to relieve her back pain two months before symptom onset, which was considered to be associated with this infection episode. After admission to the hospital, neurosurgeons performed emergent decompression and debridement. She was treated with intravenous ceftriaxone for four weeks, followed by oral ciprofloxacin for another eight weeks. The patient recovered well without any sequelae and had no relapse of infection at least six months after the end of treatment. In addition to the case report, we reviewed the literature for reported cases caused by R. mucosa. Our experience suggests that clinicians should include R. mucosa as one of the possible healthcare-associated pathogens among individuals who have undergone transdermal procedures. We believe that this article will help clinicians better recognize R. mucosa infection.